Results From an Italian Expanded Access Program on Cannabidiol Treatment in Highly Refractory Dravet Syndrome and Lennox–Gastaut Syndrome - Iannone, Luigi Francesco; Arena, Gabriele; Battaglia, Domenica; Bisulli, Francesca; Bonanni, Paolo; Boni, Antonella; Canevini, Maria Paola; Cantalupo, Gaetano; Cesaroni, Elisabetta; Contin, Manuela; Coppola, Antonietta; Cordelli, Duccio Maria; et al. (Frontiers in Neurology, 2021)
Background: Purified cannabidiol (CBD) was administered to highly refractory patients with Dravet (DS) or Lennox-Gastaut (LGS) syndromes in an ongoing expanded access program (EAP). Herein, we report interim results on CBD safety and seizure outcomes in patients treated for a 12-month-period. Material and Methods: Thirty centres were enrolled from December 2018 to December 2019 within the open-label prospective EAP up to a maximum of 25 mg/kg/day. Adverse effects and liver function tests were assessed after 2 weeks, 1, 3 and 6 months of treatment, and periodically thereafter. Seizure endpoints were the percentage of patients with ≥50% and 100% reduction in seizures compared to baseline. Results: A total of 93 patients were enrolled and included in the safety analysis. Eighty-two patients (27 [32.9%] DS, 55 [67.1%] LGS) with at least 3 months of treatment have been included in the effectiveness analysis; median previously failed antiseizure medications was 8. Paediatric and adult patients were uniformly represented in the cohort. At 12 months follow-up (n = 51/82, 62.2%), compared to the 28-day baseline period, the percentage of patients with at least a 50% reduction in seizure frequency was 49.0% (3.9% seizure-free). Retention rate was similar according to diagnosis while we found an increased number of patients remaining under treatment in the adult group. CBD was mostly co-administered with valproic acid (62.2%) and clobazam (41.5%). In the safety dataset, twenty-nine (31.2%) dropped out: reasons were lack of efficacy (16 [17.2%]), AEs (12 [12.9%]) and 1 met withdrawal criteria (1.1%). Most reported AEs were somnolence (22.6%) and diarrhoea (11.9%), followed by transaminase elevation and loss of appetite. Conclusions: CBD is associated with improved seizure control also in a considerable proportion of highly refractory patients with DS and LGS independently from clobazam use. Overall, CBD safety and effectiveness are not dose-related in this cohort.